Aspirin Hypersensitivity in Patients Undergoing Percutaneous Coronary Intervention. What Should We be Doing? - Kassimis, George; Raina, Tushar; Alexopoulos, Dimitrios (Current Vascular Pharmacology, 2019)
Aspirin plays a pivotal role in the management of patients with Coronary Artery Disease (CAD) with well-recognised benefits of reducing recurrent myocardial infarction and minimising the risk of stent thrombosis for those undergoing Percutaneous Coronary Intervention (PCI). Dual antiplatelet therapy is mandated for patients undergoing PCI and typically consists of aspirin and a P2Y12 receptor antagonist. Aspirin hypersensitivity poses a significant clinical dilemma, as the safety and efficacy of oral antiplatelet combinations that exclude aspirin have not been validated. Although, genuine hypersensitivity to aspirin is encountered infrequently, it can be challenging when managing patients with concomitant CAD given the paucity of safe and effective alternatives. Aspirin desensitization is a potential and safe option but may not always be practical. This review aims to highlight the challenges of aspirin hypersensitivity in patients undergoing PCI and propose a treatment algorithm to address this issue in clinical practice.
Keywords: desensitization